Monopoly à la Hotelling - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
In this short note, the behaviour of a monopolist in a horizontally differentiated market is analysed. It turns out that her incentive to differentiate is nihil, while both the optimal location choice and the optimal pricing rule depend on the relative size of the parameters involved in the model.
Keywords: 330